Diversity of the genus Trichoderma (Hypocraceae) in a Natural Protected Area in Tabasco, Mexico - Sánchez Hernández, Litzajaya; Arias Mota, Rosa María; Rosique Gil, José Edmundo; Pacheco Figueroa, Coral Jazvel (Instituto de Ecología, A.C., 2018)
Background and Aims: The state of Tabasco has lost more than 95% of its original vegetation cover. Currently, this trend shows no sign of reversing. The Agua Blanca State Park (PEAB) is gravely affected by anthropogenic activities, such as agriculture and extensive livestock farming. The objective of this study was to evaluate the diversity and dominance of species of the genus Trichoderma within the ABSP in sites with different degrees of disturbance. The genus Trichoderma is a fungi of division Ascomycota and the family Hypocraceae.Methods: Trichoderma colonies were extracted from three sites (conserved, semiconserved and disturbed) using the soil particle-washing technique. For the taxonomic identification of the isolated species, microcultures and semipermanent slides were prepared. The slides were viewed under a compound microscope. Fungal identifications were made with the aid of specific taxonomic keys.Key results: Two hundred and nine colonies belonging to 13 species of the Trichoderma genus were isolated; four of these species represent the first records for the state of Tabasco. The diversity index was significantly higher in the disturbed plot. The high values of abundance and diversity in the plot with the greatest degree of disturbance were significantly related with the soil carbon content. The semiconserved and disturbed plots were characterized by the dominance of more than two species and presented the greatest number of rare species. The dominant species during the sampling were Trichoderma piluliferum, T. koningii and T. virens and T. aureviride, T. atroviride and T. asperellum.Conclusions: The ABSP contains a high diversity of species of the genus Trichoderma. According to the results obtained for this area, agricultural activity did not significantly influence diversity or the number of Trichoderma colonies; however, these disturbances showed an effect on species dominance.